Diagnostic predictive value of Xpert Bladder Cancer Monitor in the follow-up of patients affected by non-muscle invasive bladder cancer. Issue 2 (24th October 2018) - D´Elia, Carolina; Pycha, Alexander; Folchini, Decio M; Mian, Christine; Hanspeter, Esther; Schwienbacher, Christine; Vjaters, Egils; Pycha, Armin; Trenti, Emanuela
Abstract : Aims: Cystoscopy and urine cytology represent the gold standard for monitoring superficial bladder cancer (BC). Xpert BC Monitor is a new urinary marker based on the evaluation of five target mRNAs overexpressed in patients with bladder cancer. The aim of our study was to evaluate the diagnostic accuracy of Xpert BC Monitor in follow-up of patients with non-muscle invasive bladder cancer (NMIBC). Methods: 230 patients were included in this prospective study. Xpert BC Monitor cut-off was set to 0.5. Sensitivity, specificity, positive predictive value (PPV) and negative predictive value (NPV) of cytology, Xpert BC Monitor and their combination were calculated and compared with cystoscopy/histology. Results: 52/230 patients showed a NMIBC recurrence, 45 low grade (LG) and 7 high grade (HG). Overall sensitivity was 11.5% for cytology, 46.2% for Xpert BC Monitor and 48.1% for the two tests combined. Sensitivity of cytology increased from 4.4% in LG to 57.1% in HG tumours whereas for the Xpert BC Monitor it was 40% in LG and 85.7% in HG tumours. Combined cytology and Xpert BC Monitor yielded an overall sensitivity of 42% for LG and 85.7% for HG. Overall specificity was 97.2% for cytology, 77% for Xpert BC Monitor and 75.8% for the two tests. Conclusions: Sensitivity for the Xpert BC Monitor Test was significantly higher than for cytology. The test performed very well in terms of specificity but could not reach the value of cytology, while PPV and NPV performed approximately the same for both tests.